Overview of Mitigation Programs for Cattle Diseases in Austria - Roch, Franz-Ferdinand; Conrady, Beate (Frontiers in Veterinary Science, 2021)
The non-regulation of animal diseases due to missing regulation at the EU level enable Member States to implement mitigation programmes based on their own country-specific conditions such as priority settings of the governments, availability of financial resources, and epidemiological situation. This can result in a heterogeneous distribution of mitigation activities and prevalence levels within and/or between countries which can cause difficulties for intra-community trade. This paper aims to describe the past, current and future mitigation activities and associated prevalence levels for four non-regulated animal diseases i.e. enzootic bovine leukosis (EBL), infectious bovine rhinotracheitis/infectious pustular vulvovaginitis (IBR/IPV), bovine viral diarrhoea (BVD), and bluetongue disease (BT) for Austria. Over a period of 40 years (1978-2020), regulations concerning EBL, IBR/IPV, BVD and BT were retraced to analyse the changes of legislation, focusing on sampling, testing and mitigation activities in Austria, and were linked to the collected diagnostic testing results. The study results clearly demonstrate the adaption of the legislation by the Austrian governments in dependency of the epidemiological situations. Furthermore, our study shows that, related to the forthcoming Animal Health Law on 21 April 2021, Austria has a good initial situation to achieve disease-free status and/or free from infection status based on the current available epidemiological situation and previous implemented mitigation activities. The study results presented here are intended to contribute to a better comparison of the eradication status across the European countries for non-EU regulated cattle diseases by providing information about the mitigation activities and data of testing results over a period of 40 years.